2003
DOI: 10.1074/jbc.m310130200
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Basis of Carnitine Palmitoyltransferase 1A Deficiency

Abstract: Carnitine palmitoyltransferase 1A (CPT1A) is the key regulatory enzyme of hepatic long-chain fatty acid ␤-oxidation. Human CPT1A deficiency is characterized by recurrent attacks of hypoketotic hypoglycemia. We presently analyzed at both the functional and structural levels five missense mutations identified in three CPT1A-deficient patients, namely A275T, A414V, Y498C, G709E, and G710E. Heterologous expression in Saccharomyces cerevisiae permitted to validate them as disease-causing mutations. To gain further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…New discoveries are the association of the PTPN22 phosphatase allele with rheumatoid arthritis (76) and a number of other autoimmune diseases, and of the association of two gene variants, the DDX5 Ser480Ala polymorphism of a RNA helicase (ATPase) involved in RNA unwinding and RNA binding (77), and the carnitine palmitoyltransferase 1a Ala275Thr polymorphism (78), with advanced hepatic fibrosis in hepatitis C, suggesting that it may be possible to characterize persons with NAFLD who are at 10-fold higher risk of progression and hence in need of treatment. These genes may lead to drug discovery and may allow optimal risk stratification for clinical trials.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…New discoveries are the association of the PTPN22 phosphatase allele with rheumatoid arthritis (76) and a number of other autoimmune diseases, and of the association of two gene variants, the DDX5 Ser480Ala polymorphism of a RNA helicase (ATPase) involved in RNA unwinding and RNA binding (77), and the carnitine palmitoyltransferase 1a Ala275Thr polymorphism (78), with advanced hepatic fibrosis in hepatitis C, suggesting that it may be possible to characterize persons with NAFLD who are at 10-fold higher risk of progression and hence in need of treatment. These genes may lead to drug discovery and may allow optimal risk stratification for clinical trials.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…These conserved regions are sometimes referred to as the structural determinants (SD) of the proteins. 3 It has also been demonstrated that the residues involved in the folding nuclei of the proteins are evolutionarily conserved. 4 However, significant controversy exists in this regard in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Reticulocalbin (Rcn1), which is distributed predominantly in endocrine and exocrine organs, is one member of the Ca 2+ -binding proteins in the secretory pathway [24]. Carnitinine palmitoyltransferase 1A (Cpt1a) is the key regulatory enzyme of hepatic long-chain fatty acid β-oxidation [25]. Cpt1A is also known to regulate apoptotic processes [26].…”
Section: Highly Expressed Genes and Pathways In Both Pc And Rzmentioning
confidence: 99%